Analysing the fate of nanopesticides in soil and the applicability of regulatory protocols using a polymer-based nanoformulation of atrazine - Kah, Melanie; Machinski, Patrick; Koerner, Petra; Tiede, Karen; Grillo, Renato [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Hofmann, Thilo (Springer, 2014)
For the first time, regulatory protocols defined in the OECD guidelines were applied to determine the fate properties of a nanopesticide in two agricultural soils with contrasting characteristics. The nanoformulation studied had no effect on the degradation kinetics of atrazine indicating that (1) the release of atrazine from the polymer nanocarriers occurred rapidly relative to the degradation kinetics (half-lives 36-53 days) and/or that (2) atrazine associated with the nanocarriers was subject to biotic or abiotic degradation. Sorption coefficients, derived from a batch and a centrifugation technique at a realistic soil-to-solution ratio, were higher for the nanoformulated atrazine than for the pure active ingredient. Results indicate that the nanoformulation had an effect on the fate of atrazine. However, since the protocols applied were designed to assess solutes, conclusions about the transport of atrazine loaded onto the nanocarriers should be made extremely cautiously. The centrifugation method applied over time (here over 7 days) appears to be a useful tool to indirectly assess the durability of nanopesticides under realistic soil-to-solution ratios and estimate the period of time during which an influence on the fate of the active ingredient may be expected. More detailed investigations into the bioavailability and durability of nanopesticides are necessary and will require the development of novel methods suitable to address both the "nano" and "organic" characteristics of polymer-based nanopesticides.
Keywords: Pesticide; Nanoparticle; Sorption; Degradation; OECD; Risk assessment; Nanocapsule; Plant protection